In patients with suspected rheumatoid arthritis, does the use of musculoskeletal ultrasound increase the ability of rheumatologists to confirm or rule out a diagnosis of rheumatoid arthritis at an earlier stage compared to routine diagnostic assessment? : in response to an enquiry from the Scottish Society for Rheumatology.: in response to an enquiry from the Scottish Society for Rheumatology. (2017) - Unknown
No abstract available